A bird in the hand is better than two in the bush: Investigating the relationship between financial slack and profitability in business groups - Vivien Lefebvre (BRQ Business Research Quarterly, 2024)
Using arguments from the behavioral theory of the firm, agency theory, and the literature on internal capital markets, this article investigates the relationship between financial slack and firms' profitability in standalone versus business group-affiliated firms. Using a large sample of French privately held firms, we show that there is a quadratic, inverse U-shape relationship between financial slack and profitability for privately held firms. We observe that the relation is steeper for business group affiliated firms than for standalone firms, which is consistent with the idea that firms in business groups are in competition for the business groups resources. Moreover, we explore whether business groups characteristics and position and weight of a given affiliated firm in the business group organization influence the impact of financial slack on profitability. Our results show that for firms that are closest to the business group head firm and that have a higher weight in the business groups, the quadratic, inverse U-shaped relationship is steeper. These findings suggest that the bargaining power that firms have in business groups plays an important role in explaining the relation between financial slack and profitability
Keywords: 650; Business groups; financial slack; performance; privately held firms